Perapan Metode Double Exponential Smoothing pada Prediksi Nilai Tukar Petani di Provinsi Sumatra Barat Tahun 2023 - Yulia, Rahma; Jannah, Miftahul; Syafi'i, Mohamad (JOSTECH Journal of Science and Technology, 2024)
West Sumatra is one of the provinces in Indonesia where the agricultural sector is very important for the regional economy. To encourage the development of the agricultural sector, an appropriate strategy is needed for each location. One of the efforts to encourage the development of the agricultural sector is to pay attention to the availability of agricultural facilities and infrastructure, so that there are no obstacles for producers that increase production costs and harm farmers. The purpose of this study was to determine the model and prediction results of Farmer Exchange Rate in West Sumatra using the Double Exponential Smoothing Method from January 2023 to June 2023. The prediction equation for NTP in West Sumatra Province in 2023 obtained is 〖 F〗_(t+m)=110,5049+(m)0,1773with a value of α = 0.99, β = 0.0115 and MAPE value = 0.99%. The Exchange Rate in West Sumatra from January 2023 to June 2023 tends to increase. The increasing Farmer Exchange Rate in West Sumatra can have a positive impact on the agricultural sector and improve the economic welfare of farmers.